Políticas Públicas para la gestión de conflictos: entre la institucionalización y el estancamiento - Huamani Ober, Giselle (2022)
In this article, the authors analyze the role of the various conflict management strategies proposed by Peruvian governments over the last twenty years from an approach based on public policies and their sustainability. First, they present the phases of the public problem and its relationship with the public policy production process. Secondly, the development presented during the presidential administrations in relation to conflict management and the production of related public policies is analyzed. Finally, the pertinent conclusions are presented.